Cristais líquidos policatenares contendo duas unidades acilhidrazona: mesomorfismo, fotoisomerização e gelificação - Oliveira, Wilson Aparecido de (2021)
Even though relatively less explored in the liquid crystalline field, Acylhydrazones have been showing their relevance as photochromic group, due their easy synthesis, robustness, capable of form intermolecular H-bonds and reversible E-Z photoisomerization. To expand the current knowledge about the use of Acylhydrazones in liquid crystalline field, six new molecules where planned and synthesized, all of them with two Acylhydrazones units at the mesogenic center, something not reported up to now. In addition, each molecule has systematic structural changes, as the change in the number of alkoxy chains, rigid core size and the direction of the acylhydrazones units, which allowed a better assessment of how each alteration changed the thermal and photophysical behavior. After the synthesis, the molecules had their structure and purity confirmed by H¹-NMR analysis. POM, DSC, XRD and SAXS (using synchrotron radiation) investigations confirmed the liquid crystalline behavior to five compounds, with most of them showing Colh mesomorphism, while one compound preferred to adopt a Cubbi mesophase. Investigations confirm a reversible E-Z photoisomerization, in chloroform solution. Interestingly, despite the isomeric structure, lower transition temperatures, as well a faster photoisomerization were observed for molecules derived from terephthaldehyde as central unit than the terephthaloylhydrazide one. In addition, the rigid core expansion influenced negatively in the liquid crystalline behavior, due to the significant rise in transition temperatures. Last but not least, were determined that certain compounds were able to form stable gel in toluene, while they also were able to photoisomerize, since the gel broke up after this process, but, returning to the gelled form after heating. In short, the work has shown how promising and versatile the acylhydrazone group can be as liquid crystals rigid cores, being able to induce different forms of self-organization, influence photochromism and gelation. Futhermore, the use of two acylhydrazone units resulted in interesting characteristics, which were significantly changed depending on the direction of the group.